Izzivi in sodobni pristopi k zdravljenju atopijskega dermatitisa - Vitek, Mercedes (Zdravniški vestnik, 2023)
Atopic dermatitis is the most common chronic inflammatory skin disease, characterized by changes in skin structure manifesting through red, dry and scaly areas accompanied by itching. Due to its complexity, the disease represents a considerable therapeutic challenge. Thus, up-to-date treatment guidelines emphasise the importance of comprehensive treatment. Regular and proper skincare with cosmetic products containing active ingredients that restore impaired skin barrier function through various mechanisms is of great importance. Further, depending on the degree of inflammation and the extent of skin lesions, drugs for local or systemic treatment are required. According to the standard therapeutic modalities, drugs for local therapy are used as long as the patient responds. Typically, active ingredients for dermal administration intended for active skincare and/or therapy are incorporated into conventional dosage forms such as ointments, creams, dermal solutions, and emulsions. However, in recent years major advances have been made toward developing innovative lipid-based delivery systems, such as lyotropic liquid crystals, micro- and nano-emulsions, vesicular systems, and lipid nanoparticles. The present paper systematically reviews active ingredients for skincare of atopic skin along with drugs and dosage forms registered in Slovenia for the treatment of atopic dermatitis . Concurrently, attractive scientific researches, patent publications and new achievements in innovative lipid-based delivery systems are presented, proving their unique advantages that enable patient-friendly treatment and improved therapeutic outcomes.
Keywords: active skin care; aktivna nega kože; atopic dermatitis; atopijski dermatitis; bolezni kože; corticosteroides; Dostavni sistemi; kortikosteroidi; lipid-based delivery systems; lipidni dostavni sistemi; medicines; skin diseases; zdravila